2022
DOI: 10.3390/diagnostics12020242
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Experience Measures for Colonoscopy: A Systematic Review and Meta-Ethnography

Abstract: Patient experience is defined as a major quality indicator that should be routinely measured during and after a colonoscopy, according to current ESGE guidelines. There is no standard approach measuring patient experience after the procedure and the comparative performance of the different colonoscopy-specific patient-reported experience measures (PREMs) is unclear. Therefore, the aim was to develop a conceptual model describing how patients experience a colonoscopy, and to compare the model against colonoscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…A systematic review of patient-reported experience measures for colonoscopy and meta-ethnography identified five key patient experience domains that should be encapsulated in a patient-reported measures set: health motivation, discomfort, access to information, a caring clinician-patient relationship and patient understanding. These domains need to be considered temporally, occurring before the procedure, during the procedure and after the procedure 15. A recently published validated measures set, the Newcastle ENDOPREM questionnaire, consists of 54 questions derived from semi-structured interviews which assess patient experience across five temporal procedural stages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review of patient-reported experience measures for colonoscopy and meta-ethnography identified five key patient experience domains that should be encapsulated in a patient-reported measures set: health motivation, discomfort, access to information, a caring clinician-patient relationship and patient understanding. These domains need to be considered temporally, occurring before the procedure, during the procedure and after the procedure 15. A recently published validated measures set, the Newcastle ENDOPREM questionnaire, consists of 54 questions derived from semi-structured interviews which assess patient experience across five temporal procedural stages.…”
Section: Introductionmentioning
confidence: 99%
“…These domains need to be considered temporally, occurring before the procedure, during the procedure and after the procedure. 15 A recently published validated measures set, the Newcastle ENDOPREM questionnaire, consists of 54 questions derived from semi-structured interviews which assess patient experience across five temporal procedural stages. These interviews identified six key themes assessed by the ENDOPREM questionnaire: anxiety, expectations, choice and control, communication and information, embarrassment and dignity and comfort.…”
Section: Introductionmentioning
confidence: 99%
“…Several reviews of patient-reported experiences of colonoscopy have been conducted; however, they often combine the perspectives of patients with those of healthcare professionals, making it difficult to determine the extent to which the results reflect the experiences of patients themselves 16 20. Others, meanwhile, have not been specific to the screening context, and have included patients’ experiences from surveillance programmes, making it difficult to establish what factors are associated with experiences among adults undergoing colonoscopy as a diagnostic investigation following a positive screening result, specifically 21. Further, several reviews combined more than one test procedure (eg, CTC) and did not focus on colonoscopy itself, or focused on colonoscopy as a primary screening test22 23/focused on patients’ experience with the stool test and not the diagnostic test 5 24…”
Section: Introductionmentioning
confidence: 99%
“…Colonoscopy is an endoscopic examination method used in the diagnosis, treatment, and followup of colon diseases and in patients who need colorectal cancer screening. 1,2 Colonoscopy is considered the gold standard for detecting and removing polyps and adenomas in the colorectum. However, colonoscopy is regarded to be a rather invasive procedure.…”
mentioning
confidence: 99%
“…[16][17][18][19]22,23 Nevertheless, although there are studies reporting that the embarrassment experienced by patients prevents the control of colonoscopy-related anxiety and pain and adversely affects the patient comfort, no specific research has been found evaluating the effect of nature-based sounds on embarrassment. 2,7 The effect of nature-based sound is reported to be not specific to a particular geography, to be able to appeal to all cultures, and to create positive emotional effects in patients by reflecting the well-being of the natural environment. 16 However, no peculiar studies have been found showing its effect on colonoscopy-related anxiety, pain, and embarrassment.…”
mentioning
confidence: 99%